Transfer of business, trade or undertaking and its effects on contract of employment - Mohlabi, Glynn Stephen Mabuela (University of Limpopo, 2010)
Refer to document
Thesis (LL.M. (Labour law)) --University of Limpopo, 2010.
Keywords: Transfer of business; Contract of employment; Business enterprises -- Registration and transfer; Sale of business